Electronic Government Policy Implementation in Public Services in Tangerang District, Banten Province - Soma Atmaja; Muh. Ilham; Mansyur Achmad; Andi Azikin (Faculty of Law, Universitas Pekalongan, 2025)
The author focuses on the implementation of e-government policies on online licensing services in the form of the Online Single Submission (OSS) and sipinter application. The aim of this research was to discover and evaluate how e-government policies are put into practice and to introduce a fresh approach for implementing these policies in public services in the licensing sector at DPMPTSP Tangerang Regency. The study employed a qualitative research method with a descriptive approach and an inductive strategy based on Edward III's theory. Different methods for collecting data include conducting interviews, observing, and documenting information. The results show that the implementation of egovernment policies in the Tangerang Regency DPMPTSP through the Online Single Submission (OSS) and sipinter application each has its own advantages and disadvantages. In terms of communication and resources, it has been going well, but there are some things that need to be improved in terms of disposition and bureaucratic structure. The implementation of e-government policies at DPMPTSP Tangerang Regency has been going well but there are several obstacles that must be addressed to optimise online licensing services through a new model of sipinter.